The features of training the teachers the technology of professional activities under present circumstances (Pedagogy of Higher and Secondary Education, 2014)
Horbatyuk R. M. The features of training the teachers the technology of professional activities under present circumstances.This paper is an attempt to justify the features of training future technology teachers the professional activities based on modern information and communication technologies. Curriculum and qualification characteristics at each stage of educational experts are defined, a set of psychological, educational, social, general technical and special subjects that form the professional relationship skills and develop creative minds are presented. The course for training technology teachers is implemented, it discloses the special features of the specialty, refine knowledge by accepting the assimilation of information and communication technologies during the study of general and professionally oriented disciplines. The introduction of the educational process of modern information and communication technology using active forms and methods to create a predictive information environment is shown, that provides educational process being more interactive.
Keywords: teaching technologies; information and communication technologies; skills; training; professional activity